Restrictions and New Possibilities of Technical and Conservation Diagnostics of Wood in Heritage Buildings - Drobiec, Joanna; Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Identifying the mechanical properties of wood in existing buildings allows the search for an effective way to renovate wooden structures. Tests conducted on the historic structure's tissue preclude the use of destructive testing. Individual elements of the structure can be subjected to non-destructive testing (NDT) conducted in situ.
Keywords: diagnostics of wooden structures; non-destructive testing; ultrasonic method; sclerometric method; roof truss construction